2007
DOI: 10.1007/s11249-007-9245-6
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurement of Fluid Film Thickness in Machining

Abstract: A novel method using luminescent molecule sensors is described for in situ measurement of fluid film thickness along the tool rake face in machining. The method uses an optically transparent sapphire tool to access the rake face, and measurement of radiation emitted by luminescing molecules dispersed in a machining fluid. By measuring the intensity of the emission, the film thickness is estimated. Implications for tool-chip contact boundary conditions and near-dry machining are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These optical studies rely on a controlled laboratory environment and lubrication-free conditions (e.g. sapphire tool [4,5]). To move towards realistic machining applications in real processes, a different measurement approach is needed.…”
Section: Introductionmentioning
confidence: 99%
“…These optical studies rely on a controlled laboratory environment and lubrication-free conditions (e.g. sapphire tool [4,5]). To move towards realistic machining applications in real processes, a different measurement approach is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials do not have good oleophobic properties. Huang et al 14 found that during processing, the thickness of the film near a cutting edge was about 15 mm, and the thickness of the film at other positions could reach about 25 mm. When Qin 15 studied the measurement method of lubricating oil film thickness, the measured oil film thickness was about 30 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The cutting velocity varies continuously in this modulation configuration. In particular, the direction of instantaneous velocity is reversed and the tool-chip contact is completely disrupted (separation of tool from chip) during each cycle of modulation when the superimposed modulation velocity exceeds the mean (steady) cutting velocity, that is when ωA>V, where x is the angular modulation frequency and 2A is the peak-to-peak amplitude [8]. In practice, ωA would need to be increased beyond V to account for the compliance of the system.…”
Section: Introductionmentioning
confidence: 99%